CORRELATION BETWEEN CORPORATE GOVERNANCE CHARACTERISTICS AND FINANCIAL PERFORMANCE OF THE COMPANIES - Ana Maria Alexie (Annals of the University of Craiova: Economic Sciences Series, 2020)
Being considered an important instrument in ensuring prosperity of the companies, the corporate governance represents a topic which has aroused interest of numerous disciplines. The aim of this work is to study the relationship between governance characteristics and the financial performance Exchange (Return On Assets (ROA) and the Return On Equity (ROE) ) of the entities listed on Bucharest Stock (BVB). The research is carried out on a sample of 31 companies, during 3 years (2016-2018). The results of this analysis indicate a positive relationship existence between the variable represented by the dimension of the Management, and the performance of the companies expressed through ROA and ROE. A positive relationship has been obtained between the compliance rank with the Corporate Governance Code (CGC) and the financial performance of the entities listed.